Probabilistic Poly Degenerate r-Stirling Numbers of the Second Kind and r-Bell Polynomials (European Journal of Pure and Applied Mathematics, 2025)
We introduce degenerate poly r-Stirling numbers of the second kind and poly r-Bell polynomials by using degenerate polyexponential function and investigate some properties of these number and polynomials.
Keywords: Stirling numbers of the second kind,; BELL POLYNOMIAL